2020
DOI: 10.3389/fpsyg.2020.566222
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Team Role- and Character Strengths-Balance With Individual and Team-Level Satisfaction and Performance

Abstract: Teamwork has been argued to play an increasingly important role in numerous jobs, and several studies focused on the effects of team composition for work-related outcomes. Recent research has also identified individuals’ character strengths and positive team roles (e.g., idea creator and relationship manager) as conducive to work-related outcomes. However, there is a scarcity of research on the role of character strengths or positive team roles on the level of teams. In the present study, we extend theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Early Adolesc. 39, 864-903. doi: 10.1177/0272431618791286 Wagner, L., Gander, F., Proyer, R. T., and Ruch, W. (2020a). Character strengths and PERMA: investigating the relationships of character strengths with a multidimensional framework of well-Being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early Adolesc. 39, 864-903. doi: 10.1177/0272431618791286 Wagner, L., Gander, F., Proyer, R. T., and Ruch, W. (2020a). Character strengths and PERMA: investigating the relationships of character strengths with a multidimensional framework of well-Being.…”
Section: Discussionmentioning
confidence: 99%
“…Character strengths have also been shown to relate to adaptive coping strategies in the workplace and lower levels of work-related stress or burnout (Harzer and Ruch, 2015;Allan et al, 2017). Further, some character strengths go along with better self-and supervisor-rated work performance (Harzer and Ruch, 2014;Gander et al, 2020a), including both task performance and contextual performance. Finally, differences in character strengths have been observed in working versus retired individuals after controlling for age in a sample representing middle adulthood to old age, although the observed effects were small (Baumann et al, 2020).…”
Section: Workmentioning
confidence: 99%
“…Willibald Ruch and his colleagues established a reliable measure of these roles as self-reported by employees, established the validity of this seven function classification, developed an algorithm that utilized all 24 VIA character strength scores for each individual, and found that this algorithm predicted which roles individuals reported as enjoying and performing well ( Ruch et al, 2016 , 2018 ). They then looked at actual work teams and discovered that balance across the team in these character strength related roles predicted self-reported and supervisor-reported measures that included quality of team experience and aspects of performance ( Gander et al, 2018 , 2020 ). For example, self-rated work satisfaction and teamwork quality were predicted by a number of character strengths, most strongly teamwork and love.…”
Section: Toward a Theory: The Character Strengths Responsementioning
confidence: 99%
“…With regard to non-linear effects, Gander et al (2020) found that certain team roles, that are differentially predicted by character strengths profiles, have a quadratic relationship with team performance, meaning too little of that role in a team hurts performance and too much of that role also hurts performance. In this same study they did not find any quadratic relationships between specific character strengths representations on a team and team performance.…”
Section: Future Researchmentioning
confidence: 99%
“…Character strengths are defined as positively-valued personality traits (Peterson & Seligman, 2004). These traits are associated with a broad array of important life outcomes, including life satisfaction across the life span (e.g., Baumann et al, 2020;, academic achievement (e.g., Lounsbury et al, 2009;Wagner & Ruch, 2015), work performance (e.g., Gander et al, 2020;Harzer & Ruch, 2014;Littman-Ovadia & Lavy, 2016), relationships (Wagner, 2019;Weber & Ruch, 2012), and health-related behaviors (Proyer et al, 2013). While character strengths are related to a variety of desirable long-term outcomes across different life domains (for an overview, see also , they may also be associated with more proximal outcomes and they could be capitalized upon to achieve specific goals or purposes.…”
mentioning
confidence: 99%